N-Alkylation by Hydrogen Borrowing: Pharmaceutical Applications and Comparison with Other Methods - Nalikezhathu, Anju; Williams, Travis J. (Synthesis, 2025)
Formation of C–N bonds is a quintessential transformation in organic synthesis. Among the various methods to access them, hydrogen borrowing catalysis offers a green, atom-economical, and cost-effective approach, with water being the sole by-product. In this reaction, amines are alkylated using alcohol coupling partners in the presence of a transition metal catalyst. Several catalytic systems have been developed and utilized in the synthesis of pharmaceutical intermediates and complex natural products, thereby replacing conventional amination reactions with hydrogen borrowing reactions that deliver improved selectivity and yield. In this short review, we compare hydrogen borrowing N-alkylation with other classical and modern C–N bond forming reactions and discuss applications in pharmaceutical synthesis.
Keywords: N-alkylation; Hydrogen borrowing; Amine alkylation; C–N bond formation; Natural products; Pharmaceutical intermediates; Catalysis